Extracorporeal Shockwave Therapy Reduces Pain and Improves Internal Rotation after Arthroscopic Capsular Release: A Randomized Clinical Trial - Zifan Lin; Hong Shao; Jun Chen; Wei Yao; Chang Liu; Zhengbiao Jin; Yunxia Li (International Journal of Clinical Practice)
Background. There is still no consensus on the treatment of frozen shoulder (FS). Clinical studies on extracorporeal shockwave therapy (ESWT) combined with arthroscopic capsular release (ACR) for FS are still lacking. Objectives. To investigate the effect of ESWT on short-term functional recovery after arthroscopic capsular release (ACR). Methods. A randomized clinical trial including 49 patients who under ACR was included. The patients were assigned to the ESWT group (n = 24) or non-ESWT group (n = 25) 2 weeks after surgery. Routine advanced rehabilitation program are given to all participants, while the ESWT group additionally received 5 times shockwave therapy. Visual analog scale (VAS) pain score, Constant score, University of California Los Angeles score (UCLA), UCLA-satisfaction, and shoulder range of motion (ROM) in four directions of flexion, abduction, internal, and external rotation were analyzed at the baseline (2 weeks postsurgery), 2 weeks, 8 weeks, and 12 weeks of follow-up. Repeated measure ANOVA is used to analyze the above outcomes. Results. A total of 46 participants completed all assessments. Pain and function improved in both groups. Comparing between the groups, we found that lower VAS pain scores and higher internal rotation were found in the ESWT group at each follow-up stage (all P<0.05, 12 weeks VAS-pain 95% CI: [ESWT: 1.55–2.19, non-ESWT: 2.11–2.76], and 12 weeks internal rotation 95% CI: [ESWT: 5.42–7.27, non-ESWT: 7.20–9.06]). Regarding functional scores, the UCLA and UCLA-satisfaction of the ESWT group was significantly higher than that of the control group at 8 weeks and 12 weeks of follow-up (all P<0.05, 12 weeks UCLA 95% CI: [ESWT: 31.94-33.45, non-ESWT: 27.94-29.45], 12 weeks UCLA-satisfaction 95% CI: [ESWT: 4.32–5.00, non-ESWT: 2.50–4.32]), but there was no significant difference in Constant (P>0.05, 12 weeks Constant 95% CI: [ESWT: 82.98-92.94, non-ESWT: 78.24–88.20]). Conclusion. Extracorporeal shockwave therapy has a good analgesic effect and improves internal rotation after arthroscopic capsular release through short-term follow-up.